A New Switched DC-Link Capacitor-based Multi-level Converter (SDC2MLC) - Jagabar Sathik, M.A. (Taylor and Francis Inc., 2017)
At present, one of the most common techniques for high power conversion in medium-voltage applications is the use of cascaded multi-level converters. In this article, a new Switched DC-Link Capacitor Multi-level converter (SDC2MLC) with considerably few numbers of power electronics switches (IGBTs) is proposed, where keeping the total harmonic distortion of the output voltage waveforms as low as possible is desired. The proposed topology is configured using two separate basic units. Each unit consists of four switches with a series-parallel combination of isolated DC sources. The performance of the presented topology for both configurations is described. The required number of switches, power diodes, gate driver circuits, and voltage stresses across the switches are compared with those of other recently published techniques. Furthermore, the operation and performance of the proposed SDC2MLC are illustrated with the aid of experimental results of a single-phase 11-level converter to clarify the viability of the proposed topology. © 2017, Copyright © Taylor & Francis Group, LLC.